2021
DOI: 10.3389/fonc.2021.691064
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Cardiac Disorders Associated With Chimeric Antigen Receptor T Cell Therapy in 126 Patients: A Single-Centre Retrospective Study

Abstract: IntroductionChimeric antigen receptor T (CAR-T) cells are effective in treating hematological malignancies. However, in patients receiving CAR-T therapy, data characterizing cardiac disorders are limited.Methods126 patients with hematologic malignancies receiving CAR-T cell therapy were analyzed to determine the impact of CAR-T therapy on occurrence of cardiac disorders, including heart failure, arrhythmias, myocardial infarction, which were defined by the Common Terminology Criteria for Adverse Events (CTCAE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…After IL-1 overproduction, the monocytes/macrophages produce IL-6, which plays a pivotal role in CRS ( 50 ). Current clinical protocols to treat CRS include glucocorticoids and/or IL-6 blockade (tocilizumab) ( 1 , 52 ), whereas preemptive or early intervention with tocilizumab has been reported to prevent severe CRS ( 53 , 54 ). IL-1 blockade (anakinra) is another promising strategy that is currently in clinical trials ( 55 ).…”
Section: Challenges Of Current Car T-cell Therapiesmentioning
confidence: 99%
“…After IL-1 overproduction, the monocytes/macrophages produce IL-6, which plays a pivotal role in CRS ( 50 ). Current clinical protocols to treat CRS include glucocorticoids and/or IL-6 blockade (tocilizumab) ( 1 , 52 ), whereas preemptive or early intervention with tocilizumab has been reported to prevent severe CRS ( 53 , 54 ). IL-1 blockade (anakinra) is another promising strategy that is currently in clinical trials ( 55 ).…”
Section: Challenges Of Current Car T-cell Therapiesmentioning
confidence: 99%
“…The patient's symptoms improved quickly and the lung inflammation gradually subsided. Besides, K. Qi et al (125) analyzed the adverse events after treatment in 126 patients with hematologic malignancies who received CAR-T cells therapy. The results showed that cardiac adverse events associated with CAR-T cells therapy were common and related to the development of CRS.…”
Section: Clinical Management and Medicationmentioning
confidence: 99%
“…11 A key approach to improving outcomes is to reduce the risk of CRS and cardiac toxicity by pre-CD19-CART reduction of leukemia burden and a preemptive approach to treating CRS. 10,12 This case demonstrates that even in a pediatric patient with complex cyanotic heart disease, CD19-CART therapy could be tolerated and is a viable option to treat high-risk or relapsed B-ALL. However, the efficacy and safety of this approach need further study.…”
mentioning
confidence: 93%